Indigenous People Carrying Capacity; Consciousness of Protecting Nature - Pamungkas, Ahmad Sopian (Jurnal Indonesia Sosial Sains, 2025)
The historical relationship between indigenous communities and their environment exemplifies sustainable coexistence, yet this balance is increasingly threatened by population growth and environmental degradation. This study examines the carrying capacity of the Wana tribe’s land in the Morowali Nature Reserve, Central Sulawesi, Indonesia, to assess its ability to support current and future populations while preserving ecological integrity. Using a mixed-methods approach, we combined geospatial analysis (ArcGIS) with ethnographic data to evaluate habitable land areas, accounting for slope constraints (0–15%) and the tribe’s customary land-use practices. Results revealed that the Wana tribe currently occupies only 955.3 hectares of the 4,660-hectare reserve, with a per-capita allocation of 2.07 hectares—five times the WHO minimum standard. However, projections indicate that the carrying capacity will be exceeded if the population reaches 2,274 individuals, risking resource depletion and ecosystem disruption. The study highlights the Wana’s sustainable practices, such as fallow periods and spiritual land protections, as vital to maintaining this equilibrium. These findings underscore the urgency of integrating indigenous knowledge into conservation policies to safeguard both cultural and environmental sustainability. By quantifying carrying capacity in a protected indigenous area, this research provides a replicable framework for similar contexts and advocates for policy support to mitigate future risks.